Same-day edit and personalization of the Catholic Wedding ritual in Nueva Ecija - Gutierrez, Guia Marie Basco
How does a modern event documentation represent a traditional ritual? In this research, I examined how the same-day edit represents the wedding ritual. Specifically, this study looked into the mediatization of Catholic wedding ritual in Nueva Ecija and how it impacts the wedding ritual. Mediatization theory and mediatized ritual guided this research as it focused on the Catholic wedding ritual in Nueva Ecija and the same-day edit videos produced by Chris Camania Photography. In using qualitative textual analysis, the study described the Catholic wedding ritual in Nueva Ecija. analyzed the same-day edit videos produced by Chris Camania Photography, compared the SDE and the Catholic wedding ritual. and was able to discuss the impact of the mediatized ritual to the Catholic wedding ritual. The study found that the event documentation went beyond the Catholic ritual. Through media logic, it emphasizes some rites more than the others to be able to create a 'personalized" narrative that evokes an overall feeling of social ritual experience. Keywords: medialization, wedding, ritual, videography, same-day edit, personalization